Establishment an echovirus 6 infection model based on hFcRn transgenic mice - Li, Fei; Fu, Yiliang; Huang, Luci; Zhang, Hanwen; Huang, Juan; Wang, Yi; Xie, Zhengde; Chen, Xiangpeng (Frontiers in Medicine, 2025)
Echovirus 6 (E6) infection, a member of enterovirus, can cause severe neurological complications, particularly viral meningitis and encephalitis in children. However, the shortage of effective animal models has substantially impeded research on its pathogenesis and the advancement of therapeutic strategies. This study established and characterized a novel E6 infection model by employing transgenic (Tg) mice carrying the human neonatal Fc receptor (hFcRn). Following intracranial injection via the foramen magnum with E6, hFcRnTg mice exhibited significantly lower survival rates, impaired weight gain, and more severe clinical manifestations compared to wild-type control. Elevated levels of virus were detected in the brain, spinal cord, and muscle tissues of hFcRnTg mice, accompanied by substantial pathological changes, including neuronal damage, glial cell proliferation, and inflammatory infiltration. Immunofluorescence analyses confirmed active viral replication in the thalamus, meninges, and hippocampus. Extensive cytokine analysis showed increased concentrations of pro-inflammatory mediators, including MCP-1, IFN-γ, and TNF-α. Transcriptomic and proteomic analyses revealed enhanced immune pathways and suppressed metabolic processes, with key proteins MyD88, Cxcl10, and Irf3 central to the host response. Notably, our findings suggest that E6 infection may engage ZBP1-centered PANoptosis, although the underlying mechanisms require further validation. This model provides a valuable tool for investigating E6 pathogenesis and evaluating potential therapeutic strategies.